36+-4k=-64+-24k

Simple and best practice solution for 36+-4k=-64+-24k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36+-4k=-64+-24k equation:


Simplifying
36 + -4k = -64 + -24k

Solving
36 + -4k = -64 + -24k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '24k' to each side of the equation.
36 + -4k + 24k = -64 + -24k + 24k

Combine like terms: -4k + 24k = 20k
36 + 20k = -64 + -24k + 24k

Combine like terms: -24k + 24k = 0
36 + 20k = -64 + 0
36 + 20k = -64

Add '-36' to each side of the equation.
36 + -36 + 20k = -64 + -36

Combine like terms: 36 + -36 = 0
0 + 20k = -64 + -36
20k = -64 + -36

Combine like terms: -64 + -36 = -100
20k = -100

Divide each side by '20'.
k = -5

Simplifying
k = -5

See similar equations:

| [c+3]=15 | | -5x-19=-13x | | 45n+7776=75 | | Hg(x)=3.08(120)sqrt+18.97 | | 10x=6.5 | | 57.95=50.45+60 | | 3n^2-10n+5=0 | | 3a+6=-10 | | 3n^2-10+5=0 | | 5(3x+5)=160 | | .3m=12 | | 7.6+-5(0.1+1.1)=1.6 | | 5x+14=2p | | Hg(x)=3.08(90)sqrt+18.97 | | 4(y+2)=10(5y) | | 1+2b+12=5b-2 | | 36-4k=-8(3k+8) | | 5+-8=-18 | | 48*4.0%*0.075/130-4*0.015= | | (X-2)(x-2)-12=0 | | 77x^2+54x+9=0 | | P-11=4.2 | | 3x-0.5y=-6.8 | | -0=-5n-2n | | -10x^2+0x+10=0 | | 2*3+x=5+x | | -2x-2=5x+9 | | x+1.5y=7.4 | | 13x^2+11x-2=0 | | -k-2+7-9k= | | -25x^2-151x-6=0 | | 7(3x+5)=119 |

Equations solver categories